Re-exploring the requirement of dietary iodine intake in Chinese female adults based on 'iodine overflow theory'. - Li, Yajie; Wang, Jun; Liu, Xiaobing; Li, Weidong; Mao, Deqian; Lu, Jiaxi; Li, Xiuwei; Tan, Hongxing; Liu, Yanyan; Yan, Junan; Yu, Wei; Guo, Chongzheng; et al. (European Journal of Nutrition, 2023)
Purpose: We re-explored the basal iodine requirement based on healthy Chinese female and a new iodine overflow theory was proposed for iodine balance study. Methods: Thirty-six Chinese healthy female adults (age 20.7 ± 1.1) were recruited for this study, which included 40 days low iodine depletion period and six stages of 30 days supplementation period. Uniform diets with low iodine were provided and the content of iodine in the diet was regulated by dairy products. The total iodine intake from food and the total iodine excretion through 24-h urine and staged feces were completely gathered and monitored. The incremental (Δ) intake and excretion over the range were calculated. Results: The iodine intake and excretion were 13.6 μg/day and 48.6 μg/day at the first stage, respectively. The incremental iodine intakes and excretions were 21.1 μg/day to 120.3 μg/day and 25.8 μg/day to 105.4 μg/day for the supplementation stages, respectively. According to the 'iodine overflow theory', the zero iodine balance (Δ iodine intake = Δ iodine excretion) derived from a mixed effect model indicated a mean iodine intake of 52.2 μg/d (1.0 μg/d kg). The RNI for iodine to healthy Chinese female adult was 73.1 μg/d (1.4 μg/d kg). Conclusion: A daily iodine intake of 52.2 μg/d may meet the basal iodine requirement for healthy Chinese female adults, and Chinese female may need more than 20% iodine intake than male based on the 'iodine overflow theory'. The trial was registered at the Chinese Clinical Trial Registry in May 2018 (No: ChiCTR1800016184).